Authenticity in Virtual Reality for assessment and intervention in autism: A conceptual review. (November 2016) - Parsons, Sarah
Abstract: Virtual Reality (VR) technologies have shown potential for learning and assessment for children, adolescents, and adults with autism. Much of the research in this area has taken a conceptual stance of veridicality; that is, that VR offers promise because it can provide authenticity and levels of realism alongside stimulus or environmental control, or both, which may first facilitate learning and the generalization of skills to the real world, and secondly can provide experimental contexts with strong ecological validity for assessment. This conceptual review raises questions about the assumption of veridicality of VR for autism research by examining research literature that has used VR to support learning and to investigate social responding. In so doing, it provides a framework for examining the assumed relationship between virtual and real contexts in order to highlight particular features of design and interaction, as well as background characteristics of participants, that may help or hinder learning and understanding in virtual environments. The conclusions suggest there is a need for the field to systematically examine the different factors that influence responding in VR in order to understand when, and under what circumstances, the responses of individuals with autism can be considered appropriately authentic. There are also opportunities for thinking more radically about research directions by focusing on the strengths and preferences of people with autism, and promoting more participatory and inclusive approaches to research. Highlights: Virtual Reality (VR) technologies are 'potentially transformative' for education. It is assumed that VR is veridical i.e. authentic and realistic. It is argued that VR may be especially useful for individuals with autism. Challenges to the assumption of veridicality for VR for autism are highlighted. Systematic research is needed to reveal the factors that influence responding.